Microscopy and morphological characteristics of some ectoparasites of veterinary interest - Pulido-Villamarín, Adriana del Pilar (2016)
The ectoparasites significantly affect the health status of the animals due to their toxic and allergic effects that cause a detriment in their welfare and additionally may have a negative effect on feed conversion rates in farm animals. Ectoparasites can affect animals of all species and ages, being the young animals the most susceptible. The importance of a proper diagnosis of these health problems is given not only by the discomfort they generate in their hosts, but by the fact that they can transmit other pathogens. The aim of this paper was to describe some morphological characteristics of specific ectoparasites that have veterinary importance, especially under the prevailing environmental conditions in Colombia.